2004
DOI: 10.1128/aem.70.8.4604-4612.2004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Plasma Membrane Protein, Expressed in the Midgut Epithelia of Bombyx mori , That Binds to Cry1A Toxins

Abstract: We describe the properties of a novel 252-kDa protein (P252) isolated from brush border membranes of Bombyx mori. P252 was found in a Triton X-100-soluble brush border membrane vesicle fraction, suggesting that it may be a component of the midgut epithelial cell membrane. P252 was purified to homogeneity, and the amino acid sequence of two internal peptides was determined, but neither of the peptides matched protein sequences in the available databases. The apparent molecular mass of the purified protein was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 46 publications
1
46
2
1
Order By: Relevance
“…Differential lectin binding of B. mori polycalin suggests that it may have both N-and O-linked GalNAc, including terminal GalNAc, yet binding by Cry1Ac was not inhibited by GalNAc (Hossain et al, 2004), a result that contrasts with purification method reported here for the protein from H. armigera. The H. armigera polycalin has two Asn-Xaa-Ser/Thr sequons that may carry N-linked glycan, five predicted O-linked sites and a predicted GPI anchor site but a mucin-like region is not predicted.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Differential lectin binding of B. mori polycalin suggests that it may have both N-and O-linked GalNAc, including terminal GalNAc, yet binding by Cry1Ac was not inhibited by GalNAc (Hossain et al, 2004), a result that contrasts with purification method reported here for the protein from H. armigera. The H. armigera polycalin has two Asn-Xaa-Ser/Thr sequons that may carry N-linked glycan, five predicted O-linked sites and a predicted GPI anchor site but a mucin-like region is not predicted.…”
Section: Discussioncontrasting
confidence: 86%
“…This polycalin was characterised as a binding protein for chlorophyllid-A, the prosthetic group from chlorophyll (Mauchamp et al, 2006). The polycalin sequence of B. mori was subsequently matched with two peptides from a previously unidentified, very high-molecular-weight protein that bound Cry1Aa, Cry1Ab and Cry1Ac in heterologous competition binding studies (Hossain et al, 2004;Hossain et al, 2005;Pigott and Ellar, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…B. thuringiensis sotto T84A1, a gift from Dr. M. Ohba, and B. thuringiensis kurstaki HD-73 were used to prepare Cry1Aa9 and Cry1Ac1, respectively, as previously described (Hossain et al, 2004). The bacteria were cultured in 500 ml bot-tom-baffled flasks containing 100 ml NYS medium, as in Suzuki et al (1992).…”
Section: Methodsmentioning
confidence: 99%
“…The best characterized among them are the APN receptor (Pigott and Ellar, 2007) and the cadherin-like receptor (Gahan et al, 2001;Likitvivatanavong et al, 2011;Pacheco et al, 2009;Valaitis et al, 2001) identified in lepidopterans. Other putative receptors include ALP (Fernández et al, 2006;Jurat-Fuentes and Adang, 2004;Jurat-Fuentes and Adang, 2006), a 270 kD glycoconjugate (Valaitis et al, 2001), and a 252 kD protein (Hossain et al, 2004).…”
Section: )mentioning
confidence: 99%